(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:This research reviews the political history of Sharif Hassan with the Ottoman Empire during the period 1908-1913 and reviews the life of Sharif Hussein from his birth and upbringing and his relationship with Sultan Abdul Hamid II, then his appointment as Emir of the Hijaz, and then his relationship with the unionists, leading to his dispute over influence and control in the region, especially with Ibn Saud And Imam Yahya in Yemen and his position on the revolution of Imam Muhammad al-Idrisi in Asir, and finally the deterioration of his relationship with the Unionists.Keywords: Sharif Hussein, the Ottoman Empire, Britain, Al-Idrisi, Asir, Yemen